Selective gas sorption studies in metal-organic frameworks - Brown, Martyn Stewart (2016)
This thesis describes the synthesis and characterisation of several new metal-organic frameworks (MOFs). These frameworks have subsequently been used in gas sorption experiments to determine the selective adsorption of various guests.